Learner’s perspectives on competency-based medical education in pharmacology at a tertiary care teaching hospital in South India - Chakraborty, Ananya; A., Meharban; Kamath, Latha (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Competency based medical education (CBME) was implemented recently in India. The study was conducted to evaluate the perspectives of undergraduate medical students towards CBME curriculum in pharmacology at a tertiary care medical college in South India. Methods: After the completion of the curriculum, feedback was taken in a semi-structured, validated questionnaire. It was based on Kirkpatrik’s level 1 model of evaluation. Majority of the questions were framed on a 5-point Likert's scale (1 being poor to 5 being excellent). Qualitative data was collected by open ended question on additional comments. Results: The response rate was 72.8%. Majority of the participants rated the theory classes, practical classes, small group discussions, self-directed learning, integration, and assessments as good and excellent. More than 80% participants rated role play as an innovative and worthwhile concept towards mastering prescription communication. They felt that role play ignites team work, and provides confidence. Close to 90% of the participants rated the overview on emergency use authorization, orientation on drug regulators, perspectives on hydroxychloroquine prophylaxis as effective and excellent. More than 85% participants felt that AETCOM provided them insight on ethical issues, patient communication, and perspective of doctors as caregivers. 9.8% (16) participants provided comments to open ended question for feedback. Conclusions: The study provided an insight of medical undergraduates towards CBME curriculum. Further studies can be designed to look into the effectiveness of teaching learning methods based on the performance of the students, perspective of faculties with focus faculty development, and role of various stakeholders.